2010
DOI: 10.1002/dc.21325
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration diagnosis of a metastatic adult sclerosing rhabdomyosarcoma in a lymph node

Abstract: Adult sclerosing rhabdomyosarcoma (ASRMS) is a rare variant of rhabdomyosarcoma with a characteristic histological appearance of small, round cells in a dense, hyalinized stroma. Although nodal metastases of soft-tissue sarcomas are considered uncommon, up to 5% overall are associated with lymph node metastases. Nonetheless, there is little literature on the cytologic characteristics of metastatic soft-tissue sarcomas in lymph nodes, and to our knowledge, there are no reports of nodal metastasis of ASRMS diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Clinicopathologic and molecular genetic characterization of additional cases may help resolve how to classify this lesion in the future. Table 2 Summary of clinicopathologic data for 39 reported cases (including the current case) of sclerosing rhabdomyosarcoma [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Feature …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicopathologic and molecular genetic characterization of additional cases may help resolve how to classify this lesion in the future. Table 2 Summary of clinicopathologic data for 39 reported cases (including the current case) of sclerosing rhabdomyosarcoma [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Feature …”
Section: Discussionmentioning
confidence: 99%
“…These authors reported a series of unusual rhabdomyosarcoma cases, exhibiting prominent hyaline sclerosis and a pseudovascular growth pattern. Additional cases have been reported since in both adult and pediatric patients, with a marked predilection for the extremities and head and neck region [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Here we report a new case of SRMS, centered within the pterygomaxillary fossa of an adult male.…”
Section: Introductionmentioning
confidence: 86%
“…Figure 4a, b summarize key epidemiologic features of this rare variant [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The most common sites of presentation of SRMS are the extremities and the head and neck (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The cytologic features of SR have not been well characterized, and descriptions of the FNA findings of this tumor have been confined to case reports. 27,28 Aspirates of SR tend to be modestly cellular comprising fairly monotonous cells with ovoid to spindled configuration. Cytoplasm tends to be absent or indistinct, and stromal material may or may not be present (Fig.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%